2002
DOI: 10.1136/thorax.57.5.446
|View full text |Cite
|
Sign up to set email alerts
|

Randomised crossover study of the Flutter device and the active cycle of breathing technique in non-cystic fibrosis bronchiectasis

Abstract: Background: Airway clearance techniques are an important part of the routine care of patients with bronchiectasis. The use of the Flutter, a hand held pipe-like device causing oscillating positive expiratory pressure within the airways, has been proposed as an alternative to more conventional airway clearance techniques. Methods: A randomised crossover study was performed in 17 stable patients with non-cystic fibrosis bronchiectasis at home, in which 4 weeks of daily active cycle of breathing technique (ACBT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
90
0
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 12 publications
(10 reference statements)
4
90
0
8
Order By: Relevance
“…Also, the effect of physiotherapy on PFT is a matter of controversy. In studies utilizing oscillation devices and ACBT techniques, no change in PFTs have been reported [3,14,21], similar to our observations. This may be explained on the basis of the irreversible damage and bronchial dilatation despite the achievement of effective airway clearance in bronchiectasis.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Also, the effect of physiotherapy on PFT is a matter of controversy. In studies utilizing oscillation devices and ACBT techniques, no change in PFTs have been reported [3,14,21], similar to our observations. This may be explained on the basis of the irreversible damage and bronchial dilatation despite the achievement of effective airway clearance in bronchiectasis.…”
Section: Discussionsupporting
confidence: 82%
“…Recent studies have particularly focused on the comparative efficacy of ACBT and Flutter® in patients with cystic fibrosis (CF) or bronchiectasis. In one of these studies, no difference in the amount of daily sputum production could be detected, and no clear-cut data were provided concerning whether the intervention was carried out at home or at the hospital settings [3]. Similar to our study, ACBT and an oscillation device were compared in a study that lasted 3 days, and the device was found to be as effective as ACBT in terms of sputum production [16].…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations